PERANCANGAN APLIKASI PERKANTORAN ELEKTRONIK DENGAN MENGGUNAKAN METODE OBJECT ORIENTED ANALYSIS DESIGN BERBASIS WEB PADA KJPP DAR - Rivai, Samuel; Tukino, Tukino (Universitas Putera Batam, 2023)
This project aims to create an electronic office application to effectively handle administrative administration in the department. The results are then used to the OOAD-based design of electronic office applications, which might facilitate management of search data and administration. The requirements phase kicks off the OOAD stages, which then go on to analysis, design, implementation, and testing. Modeling is done using the Unified Modeling Language (UML), which also uses Use Case Diagrams, Activity Diagrams, Class Diagrams, and Sequence Diagrams. The object-oriented analysis design methodology is being used by the IT Department of PT Infineon Batam to produce electronic office applications, and it is based on a website developed using the PHP MySQL database programming language. The results of this study include the creation of an electronic office application using the OOAD methodology, which has been implemented via the localhost webserver. These results include a system analysis, interface system design, testing of the system with a black box system, and testing results with test sample cases that have been carried out to determine that this software can be used correctly.